2016
DOI: 10.1016/j.burns.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Fires in refugee and displaced persons settlements: The current situation and opportunities to improve fire prevention and control

Abstract: Introduction We aimed to describe the burden of fires in displaced persons settlements and identify interventions/innovations that might address gaps in current humanitarian guidelines. Methods We performed a systematic review of: i) academic and non-academic literature databases; and ii) guidelines from leading humanitarian agencies/initiatives regarding fire prevention/control. Results Of the 1,521 records retrieved, 131 reports described settlement fires in 31 hosting countries since 1990. These inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Independent scrutiny of the titles and abstracts by two authors (JW; ZT) identified 119 potentially relevant articles. Of those, we excluded an additional 59 studies because they failed to meet the methodological definition of systematic review as per our inclusion criteria . Therefore, a total of 60 systematic reviews formed the basis of this study …”
Section: Resultsmentioning
confidence: 99%
“…Independent scrutiny of the titles and abstracts by two authors (JW; ZT) identified 119 potentially relevant articles. Of those, we excluded an additional 59 studies because they failed to meet the methodological definition of systematic review as per our inclusion criteria . Therefore, a total of 60 systematic reviews formed the basis of this study …”
Section: Resultsmentioning
confidence: 99%
“…Stylianou et al, 2015 analysed data from England and Wales from 2003–2011, identifying a decline in burn mortality overall and a higher proportion of males than females receiving burn injuries [ 30 ]. Kazerooni et al, 2016 carried out a systematic review of academic and non-academic literature on fires in camps and settlements for refugees and displaced people worldwide, which found a 25-fold increase in the rate of settlement fires between 1990 and 2015 [ 31 ].…”
Section: Fire Data Limitations and Challengesmentioning
confidence: 99%
“…The reliance that communities have on traditional energy sources (such as open fires, kerosene lanterns and candles) exacerbates this risk (Gunning 2014 ; Lahn and Grafham 2015 ), and there are a number of examples of fires in humanitarian camps in the literature (UNHCR 2008 ; UNHCR 2013 ; Medecins Sans Frontieres 2020 ). A systematic review carried out by Kazerooni et al ( 2016 ) found that fires in refugee and displaced persons settlements (excluding urban settings where most displaced people reside) have resulted in at least 487 deaths and 790 burn injuries since 1990. While there is some evidence suggesting that the distribution of solar lamps has decreased the risk of fires (IOM 2014 ), no comprehensive studies have investigated this.…”
Section: Humanitarian Response and Energy Accessmentioning
confidence: 99%